2002
DOI: 10.1111/j.1349-7006.2002.tb02478.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Suppression of Human Cervical Cancer Cell Growth by Adenovirus Delivery of p53 in vitro: Arrest Phase of Cell Cycle Is Dependent on Cell Line

Abstract: It has been reported that overexpression of wild-type p53 protein induces suppression of tumor cell growth in vivo and in vitro. In this study, we further evaluated the differential effects of p53 delivered in an adenovirus vector on the cell growth, apoptosis and cell cycle progression in cervical cancer cell lines. We constructed a recombinant adenovirus expressing p53 and then delivered this into cervical carcinoma cell lines (CaSki, SiHa, and HeLa, HeLaS3) along with adenovirus expressing β β β β-galactosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Treatment of melittin also potently induced pro-apoptotic protein p53, Bax and caspase-3 expression but decreased anti-apoptotic protein Bcl-2 expression (27). We also observed that p53 overexpression induced apoptosis in CaSki and HeLa cells, as determined by Annexin V staining (28). This is consistent with our observation that both CaSki and HeLa cells displayed cell death upon BV treatment with the downregulation of E6/E7 protein of HPV16/18, and BV treatment behaves differently in HeLa and CaSki cells.…”
Section: Discussionsupporting
confidence: 81%
“…Treatment of melittin also potently induced pro-apoptotic protein p53, Bax and caspase-3 expression but decreased anti-apoptotic protein Bcl-2 expression (27). We also observed that p53 overexpression induced apoptosis in CaSki and HeLa cells, as determined by Annexin V staining (28). This is consistent with our observation that both CaSki and HeLa cells displayed cell death upon BV treatment with the downregulation of E6/E7 protein of HPV16/18, and BV treatment behaves differently in HeLa and CaSki cells.…”
Section: Discussionsupporting
confidence: 81%
“…1C). 30 to 50 MOI were used for nlacZ transfection 40,41 and expression experiments and second on the fact that evidence in the present study indicated that a 10:1 ratio of AdAFPep/nlacZ to AdAFPep/Rep was most appropriate for increasing transgene expression (shown later in Fig. 6).…”
Section: Methodsmentioning
confidence: 55%
“…Differential sensitivity of BRCA-2-defective Capan-1 vs. BRCA-2 normal BxPC-3 cells to ionizing radiation was attributed to the effect of BRCA-2 on DNA double-strand break repair [45,46] . Although a signifi cant difference in sensitivity between CaSki and HeLa cells has been noted previously, the underlying mechanisms remain unclear [56] . The CaSki or HeLa cell lines are both human papillomavirus (HPV)-positive, but differ in the number of HPV copies per cell (CaSki: 600 HPV copies per cell, HeLa: 50 HPV copies per cell), and consequently differ in the number of viral E6 and E7 oncoproteins; these proteins may interfere by binding with normal functions of p53 or pRb [40,56] .…”
Section: Discussionmentioning
confidence: 97%